Warm-Up Striding Under Load Does Not Improve 5-Km Time Trial Performance in Collegiate Cross-Country Runners - Eric K. O'Nea; Ryan T. Albino; Jonathan C. Swain; Dylan W. Sharp; Tara V. Boy; Lauren G. Killen (Montenegrin Sports Academy, 2020)
Post-activation potentiation has proven to be an effective strategy to enhance performance for many tasks, but little research has been conducted specifically concerning endurance sport performance. This study examined whether 5-km run performance could be improved by completing pre-run strides while wearing a 6.8 kg weighted compression garment (LOAD). A counter-balanced crossover field study design was incorporated with NCAA Division I Cross Country runners (n = 10) during coach-led, official team pre-season "speed day" practices. On Monday of Week 1, testing participants completed a course preview run and strategy session with their coach as they would do in preparation for a meet. The following two Mondays, participants completed the 5-km run as quickly as possible while blinded to pace. The team's habitual warmup routine was used, which included a 3.22-km run followed by a series of dynamic warm-up movements before four, 80-m strides were completed with LOAD or without load (CON). Average wet-bulb globe temperature for both sessions was 22.3 °C. CON did not differ (p>0.05) from LOAD in split times for kilometres 0.00-1.61 (339±13 vs 341±13 s), 1.61-3.22 (312±15 vs 312±16 s), 3.22-4.83 (339±21 vs 338±22 s), or the 0.17 km distance kick at the end of the run (71±16 vs 69±14 s). Overall time was also not improved for LOAD (1060±49 s) versus CON (1062±55 s). The ~10% body mass LOAD warm-up strategy failed to improve early, mid-, or finishing kick performance in a 5-km time-trial with well-trained runners.